2012
DOI: 10.4081/rt.2012.e37
|View full text |Cite
|
Sign up to set email alerts
|

Large Cell Neuroendocrine Carcinoma Originating from the Uterine Endometrium: A Report on Magnetic Resonance Features of 2 Cases with very Rare and Aggressive Tumor

Abstract: Neuroendocrine carcinomas (NEC) of the female genital tract are aggressive and uncommon tumors, which usually involve the uterine cervix and ovary, and are seen very rarely in the endometrium. Only less than 10 cases of large cell NEC (LCNEC) of the endometrium have been reported in the literature and their radiological findings are not well described. We report here two cases of pathologically proven LCNEC of the uterine endometrium. In both cases, the uterine body was enlarged and the tumor occupied part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Most of the tumors in these patients who have survived at least 5 years showed a dominant NECa component, accounting for 70% to 100% of the neoplasms, with a single case composed of 50% SCNECa and 50% endometrioid carcinoma, FIGO grade 1. Our findings regarding the clinical behavior of NECa of the endometrium are in agreement with previous reports, in that most cases behave aggressively 25, 10, 11, 13, 14, 23, 26, 27, 29, 54, 55 ; however, in a subset of cases the disease responds to surgical and adjuvant therapy. Of note, previous reports of endometrial NECa surviving more than 5 years have been of small cell type 6, 26, 54, 56 but there are no similar reports in LCNECa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the tumors in these patients who have survived at least 5 years showed a dominant NECa component, accounting for 70% to 100% of the neoplasms, with a single case composed of 50% SCNECa and 50% endometrioid carcinoma, FIGO grade 1. Our findings regarding the clinical behavior of NECa of the endometrium are in agreement with previous reports, in that most cases behave aggressively 25, 10, 11, 13, 14, 23, 26, 27, 29, 54, 55 ; however, in a subset of cases the disease responds to surgical and adjuvant therapy. Of note, previous reports of endometrial NECa surviving more than 5 years have been of small cell type 6, 26, 54, 56 but there are no similar reports in LCNECa.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent review of SCNECa of the gynecologic tract 2 , the ratio of advanced to early stage disease for endometrial NECa was 1.3:1. On evaluation of 14 published cases of LCNECa with staging information available 511, 13, 14 , the ratio of advanced to early stage disease in that setting was 1.8:1. It is possible that the greater number of advanced stage cases in our series (2.1:1) reflects that this is the largest collection of cases to date and/or that the cases are collected from a referral patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Makihara et al reported that the MRI findings of LCNEC are similar to those of other poorly differentiated endometrial cancers and sarcoma (9). In the present case, the preoperative diagnosis of LCNEC based on MRI and PET/CT was difficult.…”
Section: Discussionmentioning
confidence: 52%
“…Although no established treatment has been demonstrated for LCNEC of the uterine body, the majority of cases are administered multimodality therapy. With regard to chemotherapy, patients generally received six cycles of cisplatin and etoposide [11]. In the present study, the EC and LCNEC components shared identical alterations in PTEN, PIK3CA and FGFR3, although the EC component contained an additional missense mutation in FGFR3.…”
Section: Discussionmentioning
confidence: 55%
“…In dedifferentiated carcinomas, associations between cells are often accompanied by inflammatory cells that are loosely alveolar in structure, but in this case, cells were well clustered with few inflammatory cells. To the best of our knowledge, only 15 cases of endometrial LCNEC have been reported to date, including the present case (Table 2) [4][5][6][7][8][9][10][11][12]. Nine cases were pure LCNEC, and the remaining cases were associated with other types of tumors including EC (four cases), small cell NE carcinoma together with EC (one case) and papillary serous carcinoma (one case).…”
Section: Discussionmentioning
confidence: 81%